Is Tajikistan a Potential Market for Genetically Modified Potatoes? - Yormirzoev, Mirzobobo; Teuber, Ramona; Baranov, Daniil Sergeevich (Economy of Regions, 2018)
Consumer perception and willingness to pay for genetically modified foods have been extensively studied in recent years. However, until so far there is little empirical evidence for genetically modified food acceptance among Central Asian consumers. This article contributes to existing literature in this field by exploring consumers’ acceptance and willingness to pay for genetically modified potatoes in Tajikistan. A dichotomous-choice contingent valuation methodology is used as a primary empirical tool. The data was collected in a major city of Tajikistan. The results indicate that more than half of survey participants are not aware of genetically modified potatoes. Yet, the majority of consumers expressed a positive or neutral opinion about this particular product and for two-third of respondents no risks are associated with genetically modified potatoes. These results highlight that Tajik consumers seem to be less risk-averse towards genetically modified food than consumers in Europe. This study explores consumer preferences for genetically modified potatoes in Tajikistan. A contingent valuation method is applied to measure consumers’ willingness to pay for this particular genetically modified product based upon socio-demographic variables as well as predictors related to individuals’ attitudes and perceptions. Findings of the paper show the relevance and possibility to introduce and market nonconventional potato in a Central Asian market of Tajikistan.